Mechanics of crustal rocks - Lehner, Florian K.; Leroy, Yves M. (CISM Courses and Lectures, 2012)
The mechanical behaviour of the earth's upper crust enters into a great variety of questions in different areas of the geological and geophysical sciences as well as in the more applied geotechnical disciplines. This volume presents a selection of papers from a CISM course in Udine on this topic. While each of these chapters will make for a useful contribution in its own right, the present bundle also illustrates, by way of examples, the variety of theoretical concepts and tools that are currently brought to bear on earth deformation studies, ranging from reviews of poroelastic field theory to micro-mechanical and homogenization studies, chemomechanics and interfacial stability theory of soluble solids under stress, and finally to an introduction to the finite element method.